PENGARUH BAURAN PEMASARAN JASA TERHADAP LOYALITAS NASABAH TABUNGAN - Ermeila, Sri; Novianty, Dwi Eka; Harahap, Lily Rahmawati (Fakultas Ekonomi Universitas IBA, 2012)
This study aims to investigate the variables that affect the Service Marketing Mix customer loyalty Pesirah’s saving. Pesirah’s saving is one of SumselBabel Bank’s product. The sample in this study consisted of 263 customers Pesirah’s saving elected SumselBabel Bank Branch Kapten A.Rivai Palembang. Method of analysis using Multiple Regression Method. The results showed that the variables of the services marketing mix consist of Product, Price, Promoyion, Place, Human Resources, Process and Physical Facilities, partial and simultaneous effect customer loyalty. The biggest influence comes from the variable promotion of savings services, and the smallest impact from tariff savings.